(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This article aims to report the experiences with the project through the adversities during the year 2020 and the COVID-19, focusing on the scientific dissemination through audiovisual social media. In this way, there is the production of material for an awareness of the importance of preserving the biodiversity of the brazilian fauna in order to reach a general public. Scientific dissemination is one of the means of spreading scientific research, and it can be, for example, through audiovisual media such as documentaries and videos. Such audiovisual diffusion provides greater awareness of society in general, bringing biodiversity a little closer to the recipient, mainly due to the current pandemic moment. Therefore, the project seeks to reach across the walls of the university, propagating the brazilian fauna, always using images of animals in situ and reaching beyond the academic environment using the internet.